1999
DOI: 10.1111/j.1469-445x.1999.01806.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extracellular Cations on the Inward Rectifying K+ Channels Kir2.1 and Kir3.1/Kir3.4

Abstract: The effects of Ba2+, Mg2+, Ca2+ and Na+ as blocking ions were investigated in 90 and 10 mM extracellular K+ solutions on the cloned inward rectifying K+ channel Kir2.1 expressed in Xenopus oocytes. Some data were also obtained using another inward rectifying K+ channel Kir3.1/Kir3.4. The addition of Ba2+ caused a concentration-, voltage- and time-dependent block of both channels. Decreasing the extracellular K+ concentration augmented the block. The data suggest that Ba2+ blocks the channels by binding to a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…2D). BaCl 2 (500 M) abrogated the baclofen response (data not shown), which is consistent with the GABA B receptors activating GIRK channels (20,28,41). Single-cell RT-PCR on 40 neurons from four animals confirmed that 87.5 Ϯ 4.8 and 72.5 Ϯ 4.8% of NPY/AgRP neurons expressed GABA B -R1 and -R2, respectively (Fig.…”
Section: Npy/agrp Cells Respond To the Gaba B Agonist Baclofen And Exsupporting
confidence: 59%
“…2D). BaCl 2 (500 M) abrogated the baclofen response (data not shown), which is consistent with the GABA B receptors activating GIRK channels (20,28,41). Single-cell RT-PCR on 40 neurons from four animals confirmed that 87.5 Ϯ 4.8 and 72.5 Ϯ 4.8% of NPY/AgRP neurons expressed GABA B -R1 and -R2, respectively (Fig.…”
Section: Npy/agrp Cells Respond To the Gaba B Agonist Baclofen And Exsupporting
confidence: 59%
“…Figure 5 shows concentration-response curves for the inhibitory effect of Ba 2+ on ventricular I K1 and on atrial I K(ACh) . In line with a previous study, I K(ACh) was less sensitive to Ba 2+ than I K1 [29]. The EC 50 for I K1 was determined as 1.2x10 -6 M and as 2.6x10 on I K1 and I K(ACh) in a representative ventricular myocyte.…”
Section: +supporting
confidence: 64%
“…The rationale was that, under these culturing conditions, rat microglia have a prominent Kir, which is thought to be Kir2.1. 24,47 Both this Kir current and cloned Kir2.1 channels are blocked by external divalent cations; 24,47,58 thus, DVF solution might have reversed the channel block. Because Kir2.1 can be blocked by external Cs + , 59 we repeated the experiment from Figure 7A, but with 10 mM Cs + added to the DVF solution.…”
Section: Crac Mediates Soce In Microgliamentioning
confidence: 99%